2011
DOI: 10.1097/coc.0b013e3181dea993
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Recurrence in Patients With Triple-Negative Breast Cancer

Abstract: Despite significantly lower AJCC stage, patients with triple-negative breast cancer who do not undergo radiotherapy have a significantly higher risk of locoregional recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Our data are comparable with data from Dragun et al,16 who investigated the influence of PORT in TNBC patients after BCS. In this study, 53 patients (69%) received PORT.…”
Section: Discussionsupporting
confidence: 91%
“…Our data are comparable with data from Dragun et al,16 who investigated the influence of PORT in TNBC patients after BCS. In this study, 53 patients (69%) received PORT.…”
Section: Discussionsupporting
confidence: 91%
“…However, the radiation group had a higher probability of locoregional-free survival after three years (13). Abdulkarim et al found that T1-2N0 TNBC patients treated with MRM without RT had a significantly increased risk of locoregional recurrence in comparison with those treated with BCT, but there was no difference in overall survival (9).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Recent reports have suggested that this improvement also extends to patients with TNBC. 31,32 The time range included in the current cohort reflects an era during which attitudes about and indications for postmastectomy radiotherapy have been in evolution, including within our institution. As such, the group studied may not accurately reflect the impact of such therapy on LRR as managed by current protocols.…”
Section: Discussionmentioning
confidence: 99%